Effective Social Media Content Strategy to Enhance Brand Loyalty in Technology Businesses - Sutrisno, Sutrisno; Ausat, Abu Muna Almaududi; Muhamad, Lili Fadli (Institut Riset dan Publikasi Indonesia, 2024)
Consumer behavior has shifted with the advent of social media. Consumers now tend to seek information, reviews, and product recommendations through these platforms. Technology businesses must understand and leverage this change to build and maintain brand loyalty. This research aims to identify and analyze the most effective social media content strategies in enhancing brand loyalty in technology businesses, as well as providing practical recommendations for companies to implement these strategies. The research method employed is a literature review with a qualitative approach using descriptive analysis. In this study, data were collected from scholarly articles published between 2010-2024, utilizing Google Scholar as the primary source of search. This approach can provide a comprehensive understanding of the main research topic based on relevant and up-to-date empirical data. The study findings indicate that in the evolving digital era, social media has become one of the primary means for technology businesses to interact with consumers. To differentiate and build strong brand loyalty amidst increasing competition, social media content strategies should be based on a deep understanding of the target audience, consistency, authenticity, educational and informative content, active engagement, and continuous data analysis. By effectively implementing these strategies.